2022
DOI: 10.1111/jcmm.17288
|View full text |Cite
|
Sign up to set email alerts
|

ASIC1a stimulates the resistance of human hepatocellular carcinoma by promoting EMT via the AKT/GSK3β/Snail pathway driven by TGFβ/Smad signals

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…PI3K/AKT/GSK3β signaling activity is an essential regulator of diverse malignant behaviour in tumor cells ( Hu et al, 2022 ; Wang et al, 2022 ), including apoptotic induction ( Zhang Y et al, 2022 ), EMT induction ( Zhao et al, 2019 ; Jiang et al, 2020 ), and resistance to treatment ( Kashyap et al, 2018 ). Previous studies showed that the combination of PI3K/AKT inhibitor LY294002 and 5-FU could lead to higher cytotoxic efficacy by inducing a greater extent of cell apoptosis than single drug therapy ( Feng et al, 2018 ; Ni et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT/GSK3β signaling activity is an essential regulator of diverse malignant behaviour in tumor cells ( Hu et al, 2022 ; Wang et al, 2022 ), including apoptotic induction ( Zhang Y et al, 2022 ), EMT induction ( Zhao et al, 2019 ; Jiang et al, 2020 ), and resistance to treatment ( Kashyap et al, 2018 ). Previous studies showed that the combination of PI3K/AKT inhibitor LY294002 and 5-FU could lead to higher cytotoxic efficacy by inducing a greater extent of cell apoptosis than single drug therapy ( Feng et al, 2018 ; Ni et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…41 HCC cells have a strong ability to transform normal hepatic stellate cells into cancer-associated fibroblasts, and these activated fibroblasts promoted cancer progression by secreting angiogenic cytokines (MMP2, MMP9). [42][43][44] IL-6/ STAT3 also affects the progression of HCC. 45 Therefore, we hypothesized that IL-6 regulates the expression of MMP2 and MMP9 through upregulating the expression of IL-6R through the JAK2/STAT3 signalling pathway to affect the invasion and migration of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…P53 activation in colorectal cancer cells interferes with IL‐6‐induced invasion and migration through downregulation of miR‐34a‐dependent IL‐6R expression, and the IL‐6R/STAT3/ miR‐34a feedback loop promotes EMT‐mediated invasion and metastasis of colorectal cancer 41 . HCC cells have a strong ability to transform normal hepatic stellate cells into cancer‐associated fibroblasts, and these activated fibroblasts promoted cancer progression by secreting angiogenic cytokines (MMP2, MMP9) 42–44 . IL‐6/STAT3 also affects the progression of HCC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Two independent studies reported that ASIC1a is expressed in hepatocellular carcinoma (HCC) cell lines and that it is upregulated in drug resistant cells; inhibition of ASICs by amiloride or knockdown of ASIC1a by shRNA enhanced chemosensitivity whereas overexpression of ASIC1a enhanced chemoresistance of HCC cells [ 97 , 98 ]. Moreover, it was reported that pH 6.5 induced a Ca 2+ signal in HCC cells, which was inhibited by amiloride but not the Ca v -inhibitor verapamil [ 98 ].…”
Section: Asics In Hepatocellular Carcinoma – Activation Of Pi3k and Aktmentioning
confidence: 99%